To Giorgio Chittolini. Some remarks about his studies (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The essay discusses Giorgio Chittolini's studies concerning the establishment of parishes, the prominence of notaries in the documentary practices of Lombard churches, and the problems of female regular life; it also points out the genesis, interests, and outcomes of many of Chittolini’s investigations, as well as the researches prompted by them.
Keywords: Giorgio Chittolini; Middle Ages; Lombardy; Ecclesiastical Institutions